Extracellular vesicular microRNAs as potential biomarker for early detection of doxorubicin‐induced cardiotoxicity. (7th April 2020) - Beaumier, Amelie; Robinson, Sally R.; Robinson, Nicholas; Lopez, Katherine E.; Meola, Dawn M.; Barber, Lisa G.; Bulmer, Barret J.; Calvalido, Jerome; Rush, John E.; Yeri, Ashish; Das, Saumya; Yang, Vicky K.
Abstract: Background: Long‐term use of doxorubicin (DOX) is limited by cumulative dose‐dependent cardiotoxicity. Objectives: Identify plasma extracellular vesicle (EV)‐associated microRNAs (miRNAs) as a biomarker for cardiotoxicity in dogs by correlating changes with cardiac troponin I (cTnI) concentrations and, echocardiographic and histologic findings. Animals: Prospective study of 9 client‐owned dogs diagnosed with sarcoma and receiving DOX single‐agent chemotherapy (total of 5 DOX treatments). Dogs with clinically relevant metastatic disease, preexisting heart disease, or breeds predisposed to cardiomyopathy were excluded. Methods: Serum concentration of cTnI was monitored before each treatment and 1 month after the treatment completion. Echocardiography was performed before treatments 1, 3, 5, and 1 month after completion. The EV‐miRNA was isolated and sequenced before treatments 1 and 3, and 1 month after completion. Results: Linear mixed model analysis for repeated measurements was used to evaluate the effect of DOX. The miR‐107 ( P = .03) and miR‐146a ( P = .02) were significantly downregulated whereas miR‐502 ( P = .02) was upregulated. Changes in miR‐502 were significant before administration of the third chemotherapeutic dose. When stratifying miRNA expression for change in left ventricular ejection fraction, upregulation of miR‐181d was noted ( P = .01). Serum concentration of cTnI changed significantly but only 1 month after treatment completion, and concentrations correlated with left ventricular ejection fraction and left ventricular internal dimension in diastole. Conclusion and Clinical Significance: Downregulation of miR‐502 was detected before significant changes in cTnI concentrations or echocardiographic parameters. Further validation using a larger sample size will be required.